How Accountability Shapes the Impact of Government Effectiveness on Corruption Outcomes - Irvan, Muhammad Alif Nur; Amalia, Elsa (E-Jurnal Akuntansi, 2025)
This study aims to examine the effect of government effectiveness on corruption in ASEAN countries and to assess the moderating role of accountability in this relationship. Using a panel data covering the period 2013–2023, the study measures variables through the World Governance Indicators (WGI) and applies panel regression analysis. The findings show that government effectiveness has a significant negative effect on corruption, indicating that improved institutional capacity and public service delivery can effectively reduce corrupt practices. Furthermore, accountability positively moderates the relationship, suggesting that the impact of government effectiveness on corruption control is stronger in environments with greater public oversight and citizen engagement. These results support institutional theory and offer empirical evidence that successful anti-corruption reforms require the synergy of institutional strength and robust accountability mechanisms.